Trends in sports-related upper extremity injuries presenting to United States emergency departments: a retrospective analysis of national injury data - Ramey, Matthew D.; Swaminathan, Srivatsan J.; Locke, Auston R.; Koehne, Niklas H.; Schroen, Christoph A.; Swaminathan, Visweshwar G.; Corvi, John J.; Capotosto, Salvatore; Cagle, Paul J.; Hausman, Michael R. (Journal of Clinical Medicine, 2025)
Background: Across many sports, injuries to the upper extremity (UE) are prevalent due to falls on an outstretched hand (FOOSH) and overuse. This retr...
Gesehen am 28.01.2026